MANHAJ TAFSIR ISHARI IBNU AJIBAH DALAM KITAB TAFSIRNYA AL-BAHRUL MADID - Hermansyah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This paper examines the manhaj of Ibn Ajibah, a Sufi from Morocco. Of course, the teachings of Sufism that he was involved in had an influence on the interpretation of the Qur'an. But Ibn Ajibah has a commitment to unify the interpretation of the zhahiri and ishari. He does not want to be trapped in the inner interpretation which is more concerned with the inner meaning and ignores the outer interpretation in language. For this reason, the study of Ibn Ajibah's manhaj in his interpretation becomes significant to determine the extent to which Ibn Ajibah interprets the Qur'an in the ishari interpretation style